Early intravenous administration of nutritional support (IVANS) in metastatic gastric cancer patients at nutritional risk, undergoing first-line chemotherapy: study protocol of a pragmatic, randomized, multicenter, clinical trial. (February 2020) - Caccialanza, Riccardo; Cereda, Emanuele; Klersy, Catherine; Brugnatelli, Silvia; Borioli, Valeria; Ferrari, Alessandra; Caraccia, Marilisa; Lobascio, Federica; Pagani, Anna; Delfanti, Sara; Aprile, Giuseppe; Reni, Michele; et al.
Background: Malnutrition is common in cancer patients, particularly in those affected by gastrointestinal malignancies, and negatively affects treatment tolerance, survival, functional status, and quality of life (QoL). Nutritional support, including supplemental parenteral nutrition (SPN), has been recommended at the earliest opportunity in malnourished cancer patients. The limited available evidence on the efficacy of SPN in gastrointestinal cancer patients is positive, particularly with regards to QoL, body composition, and energy intake, but the evidence on survival is still scanty. Furthermore, studies regarding the early administration of SPN in combination with nutritional counseling from the beginning of first-line chemotherapy (CT) are lacking. We hypothesize that early systematic SPN in combination with nutritional counseling (NC), compared with NC alone, can benefit patients with previously untreated metastatic gastric cancer at nutritional risk undergoing first-line CT. Methods: The aim of this pragmatic, multicenter, randomized (1:1), parallel-group, open-label, controlled clinical trial is to evaluate the efficacy in terms of survival, weight maintenance, body composition, QoL and feasibility of cancer therapy of early systematic SNP. This is in combination with NC, compared with NC alone, in treatment-naïve metastatic gastric cancer patients at nutritional risk undergoing first-line CT. Discussion: Malnutrition in oncology remains an overlooked problem. Although the importance of SPN in gastrointestinal cancer patients has been acknowledged, no studies have yet evaluated the efficacy of early SPN in metastatic gastric patients undergoing CT. The present study, which guarantees the early provision of nutritional assessment and support to all the enrolled patients in accordance with the recent guidelines and recommendations, could represent one of the first proofs of the clinical effectiveness of early intensive nutritional support in cancer patients undergoing CT. This study could stimulate further large randomized trials in different cancer types, potentially resulting in the improvement of supportive care quality. Trial registration: This study is registered on ClinicalTrials.gov: NCT03949907.